HUBUNGAN DUKUNGAN KELUARGA DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIS YANG MENJALANI CAPD DI RUANG CAPD IMAM BONJOL RSUD DR. SAIFUL ANWAR MALANG - Henny Lailatut Tarwiyah ,; Andi Surya Kurniawan ,; Reny Tri Febriany , (Jurnal Cakrawala Ilmiah, 2024)
CAPD is one of the appropriate therapies for chronic kidney failure patients that can prevent death but cannot cure or fully restore kidney function. The aim of this study was to determine the relationship between family support and the quality of life of chronic kidney failure patients undergoing CAPD in the Imam Bonjol CAPD Room, Dr. Hospital. Saiful Anwar Malang. The research method used in this study is an analytical descriptive design with a cross-sectional method. The research sample is 175 CAPD patients with random sampling technique. The results of the study indicate that the majority of respondents have good support, with 152 respondents (86.9%), and high-quality life, with 157 respondents (89.7%). The Spearman's rho analysis results show a value of α < 0.05, namely (0.000), which means that there is a relationship between family support and the quality of life in chronic kidney failure patients undergoing CAPD at Dr. Saiful Anwar Malang Regional General Hospital. Nurses caring for CAPD patients are advised to enhance their understanding of the importance of family support and how to support the patient's family effectively. Regular monitoring and evaluation of nurse-family interactions with CAPD patients are recommended to ensure adequate support.